Scholars and Dollars : Politics, Economics, and the Universities of Ontario 1945-1980. - Axelrod, Paul (University of Toronto Press, 1986)
The author concludes that not only did the universities prove to be imperfect instruments of economic development, but the efforts expended in the task compromised their vital role as islands of culture and critical thought in a materialistic society.